Sampling methods and metereological factors on pests and beneficial organisms in strawberries - Benatto, Alessandra (2021)
We characterize the population dynamics of pests and beneficial organisms in strawberries to assess the impact of two meteorological factors (temperature and precipitation) and define the most appropriate method for monitoring insects in strawberries crop. Population dynamics were monitored weekly using the plant beat method and Möericke traps in Albion strawberries. Measurements were taken in organic strawberry farms over two growing seasons, from March 26, 2010 to August 23, 2010 (first season - 2009/2010) and from October 4, 2010 to March 21, 2011 (second season - 2009/2010) in the municipality of Pinhais, Paraná state, southern Brazil (25º25'S; 49º08'W). We collected a total of 7,971 pests and 1,987 beneficial organisms. The most abundant pests were Chaetosiphon fragaefolii (Cockerell) (Hemiptera: Aphididae) in the first growing season and Tetranychus urticae (Koch) (Acari: Tetranychidae) in the second. Beneficial organisms from Acari, Araneae, and Hymenoptera parasitoids predominated in both seasons. Temperature and precipitation were the the primary climatic factor associated with the population variation of aphids. Populations of C. fragaefolii grew when the temperature was between 16°C and 25ºC. We found that plant beat was the fastest and most suitable method for strawberry pests monitoring since it captured insects that were effectively colonizing the plants. This study contributes to a better understanding of the entomofauna associated with cultivation of organic strawberry.